The Morphotectonic And Neotectonic Response In Apaumagida, Enarotali And Pegunungan Legare Area Papua - Gultom, Maran; George Aiwoy, Fence; Kornelis Tipawael, Theopilus; Anakotta, Saneraro (International Journal of Science, Technology & Management, 2023)
The verification of  morpho-tectonic responses  were indicated by  changing of   the lineament, the river  segment azimuth,  the mountain front  sinuoucity,  the mountain front  facet  in rock formation between  lately and early geological period,  controlled by neotectonic for  bifurcation ratio and  drainage  density in Quarternary morphometry. There are three research areas namely Apaumagida Area represented by  Permian–Triassic at coordinate 135°18’11,88” E - 135°43’20,14” E and 3°56’17,59” S - 4°8’28,44” S, Enarotali Area represented by  Cretaceous–Paleocene at coordinate 136°18’45,08” E - 136°29’42,00” E and 3°53’34,75” S - 4°5’16,03” S, and  Legare Mountain Area  represented by  Tertiary– Quarternary at coordinate 135° 28’ 54,87” E - 135° 47’ 16,80” E and 3° 25’ 31,17” S - 3° 6’ 6,25” S. Conclusion by different test and regression-correlation test for lineaments, river segments, mountain front sinousity and mountain face facet  between Permian -Triassic, Cretaceous-Palecene and Tertiary -  Quarternary are significant different  to indicated that tectonic   roled actively in geomorpho-tectonic in  research area. Furthermore,  by the neotectonic controlled, there is  similarity between bifurcation ratio and drainage density in Quarternary  indicated that  tectonic roled  actively to forms   morphology    in Central Mountain Papua.